ანტიკური წყაროები მიკენური ეპოქის არა¬ბერ¬ძენ ხალხთა შესახებ - ჩოთალიშვილი, ლელა (ლოგოსი, 2022)
According to the Ancient sources, numerous peoples and tribes of non-Greek origin, referred to as “barbarians” from a certain period, were populated in the basin of the Aegean Sea already before Greeks and also played a leading role in the continental Hellas. Nowadays, the information presented in the works of Ancient authors about non-Greek peoples and tribes living on the Aegean lands is a source of controversy among the scientific community. I believe it is partially possible to reconstruct the geographical and political situation of Aegean territory during the Bronze Age based on Ancient sources. We will try and examine the perception of ethnic, cultural and political situation of Aegeis by the Greeks in the Bronze Age. In this light it would be also interesting to perform the comparative analysis of topographical data preserved in Linear B inscriptions and Ancient Near Eastern written sources. This would aid us in deciding how real is the picture presented in the Ancient works. On the account of Linear B inscriptions, the topographical data preserved in the Egyptian and Hittite documents, and the archaeological material, it can be said that the geographical situation presented by the Ancient sources is mostly real. However, it would not be at all surprising if the records written by Ancient Greeks were not completely in accord with the geographical and political situation of Greece and Middle East in the Bronze Age, considering the significant time difference between the Mycenaean palace culture and Hellenistic and Classical Greece. This detail would undoubtedly contribute to the alteration and, hence, the imprecise nature of the information.